First national report of modified puestow technique for the treatment of recurrent acute pancreatitis in Pediatrics - Sienra, Celina; Pereira-Núñez, Diego; Juambeltz, Carlos (Cirugía del Uruguay, 2021)
The first national report of the treatment of recurrent acute pancreatitis by means of Wirsung-jejunal diversion in pediatrics is communicated. This is a patient with multiple hospital admissions for episodes of pancreatitis, with evolutionary complications of pancreatic pseudocysts, stenosis, and Wirsung duct lithiasis. Wirsung-jejunal bypass was performed by conventional route with good subsequent evolution.